Sullivanesque urban architecture and ornamentation - Schmitt, Ronald E. (Urbana : University of Illinois Press, 2002)
"Sullivanesque offers a visual and historical tour of a unique but often overlooked facet of modern American architecture derived from the work of Louis Sullivan." "Highly regarded in architecture for inspiring the Chicago School and the Prairie School, Sullivan was an unwilling instigator of the method of facade composition - later influenced by Frank Lloyd Wright, William Gray Purcell, and George G. Elmslie - that came to be known as Sullivanesque. Decorative enhancements with botanical and animal themes, Sullivan's distinctive ornamentation mitigated the hard geometries of the buildings he designed, coincided with his "form follows function" aesthetic."--Jacket.
Nature patterns in the urban landscape -- Early Sullivanesque skyscraper and prominence -- Later Sullivanesque: small buildings and anonymity -- Sullivan's former employees -- Ornament: materials, artisans, and early suppliers -- Stock Sullivanesque and the Midland Terra Cotta Company -- Sullivanesque architects in Chicago -- Chicago streets: a Sullivanesque vernacular -- Appendix: An inventory of Sullivanesque buildings.
Includes bibliographical references (p. 301-331) and index.
JSTOR
Keywords: Sullivan, Louis H., -- 1856-1924 -- Influence; Sullivan, Louis H., -- 1856-1924; Sullivan, Louis H. -- 1856-1924; Sullivan, Louis H; Architecture -- Illinois -- Chicago -- History -- 19th century; Architecture -- Illinois -- Chicago -- History -- 20th century; Architectural terra-cotta -- Illinois -- Chicago; Decoration and ornament, Architectural -- United States; Terres cuites architecturales -- Illinois -- Chicago; Décoration et ornement architecturaux -- États-Unis.; ARCHITECTURE / General; Architectural terra-cotta; Architecture; Decoration and ornament, Architectural; Influence (Literary, artistic, etc.); Illinois -- Chicago; United States; Bauornament; Architektur; Culturele invloeden; Ornamentiek; Architecten; Gebouwen; 1800-1999; History